Role of Consumer Engagement in TikTok Content and Fashion Purchase Decisions among Gen Z Muslims - Aryogi Adi Saputra; Muhammad Sholahuddin (STIE AMKOP, 2026)
The emergence of digital marketing strategies centered around social media platforms, notably TikTok, has significantly transformed the purchasing behaviors of Generation Z consumers in the fashion sector. Nonetheless, the underlying psychological processes that connect the impact of digital content to purchasing decisions remain underexplored. This research endeavors to examine the effect of TikTok content on fashion-related purchasing choices, specifically considering consumer engagement as a mediating factor among Muslim Generation Z individuals. Employing a quantitative methodology, the study surveyed 150 participants and analyzed the data using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings indicated that TikTok content exerted a positive and statistically significant influence on both consumer engagement and purchasing decisions, with consumer engagement serving as a significant mediator in these dynamics. The originality of this study resides in the incorporation of consumer engagement as a mediating construct within the framework of Muslim fashion and the Generation Z demographic. The research contributes to the theoretical discourse surrounding digital consumer behavior and offers practical insights for content-oriented marketing strategies on the TikTok platform.